The variation of gut microbiota in captive Sichuan golden snub-nosed monkeys (Rhinopithecus roxellana) from infancy to adulthood - Chen, Rong; Liu, Xinyi; Wang, Siteng; Guo, Lan; Li, Meirong; Xu, Xiaojuan; Lv, Ran; Hong, Litong; Wang, Guodong; Deng, Changlin; Sun, Weidong; Liu, Guangjin (Frontiers in Veterinary Science, 2025)
Rhinopithecus roxellana (R. roxellana) is an endangered primate species, and its infant survival rate in captivity is extremely low. In this study, we conducted a comparative analysis of the gut microbiota from 8 infants (14–18 days old), 12 juveniles/subadults (2–5 years old), and 12 adults of R. roxellana (7–14 years old), which were kept at the Nanjing Hongshan Forest Zoo in Nanjing City, Jiangsu Province, China. Through the 16S rRNA high-throughput sequencing, we found the gut microbiota richness and beta diversity in captive infant R. roxellana were significantly lower than those in the non-infant groups. The relative abundance of Firmicutes positively correlated with increasing age, whereas the abundance of Shigella/Escherichia and Akkermansia was significantly higher in the infants and exhibited a decreasing trend with age. Meanwhile, several potential pathogenic bacteria, including Clostridium perfringens, Staphylococcus aureus, and Shigella flexneri, among others, were found to be abundant in the infant samples following the cultivable bacteria isolation. This research preliminarily investigated the gut microbiota development of captive R. roxellana and provided a valuable theoretical foundation for improving the healthy breeding of captive infant R. roxellana.